Study The Sensitivity of Bacteria Isolated From Sputum of Different Antibiotics Using Kirby-Bauer Method - Alhamadani, Yousif (Journal of Biomedicine and Biochemistry, 2025)
Background: Respiratory tract infections caused by bacterial infections are among the most common health problems, exacerbated by antibiotic resistance. The aim of the study is to isolate and identify pathogenesis bacteria that responsible to respiratory system diseases from 35 samples of sputum and determine bacterial sensitivity to various antibiotics. Materials and Method: A cross-sectional study was conducted in Almuthanna Governorate-Iraq on 35 patients (26:35 male and 9:35 female) age ranged from 15 - 50 years old, the bacteria were diagnosed by physical examination, bacterial dyes and AIP examination in order to reach a final result for the diagnosed bacterial race. Antibiotics sensitivity testing was performed to determine the bacterial sensitivity using 30 different antibiotics by Kirby-Bauer disk diffusion method. Result: The study showed that there are four different species of bacteria, Streptococcus pneumonia (3:35), Mycoplasma Pneumoniae (8:35), Escherichia colli (1:35), staphylococcus aureus (23:35). As for examining of bacterial sensitivity of the isolated bacteria used in this study, showed different sensitivity to each antibiotic, Strept. pneumonia showed sensitivity to (16:30) of antibiotics and the beast effect of antibiotics is Amikacin it was 100%. M. Pneumoniae showed sensitivity to (7:30) of antibiotics and the beast effect of antibiotics is Doxycycline it was 100%. E. colli showed sensitivity to (3:30) of antibiotics and the beast effect of antibiotics are Amikacin, Imipenem and Meropenem it was 100%. S. aureus showed sensitivity to (19:30) of antibiotics and the beast effect of antibiotics is Nitrofurantionit was 100%. The results of this study can be used by assist clinicians to determine the sensitivity of bacteria to antibiotics and prescribe the appropriate antibiotic for treatment of respiratory tract infections caused by bacterial infections.